2013
DOI: 10.1179/1743676112y.0000000071
|View full text |Cite
|
Sign up to set email alerts
|

Microwave heated chemical vapour infiltration of SiC powder impregnated SiC fibre preforms

Abstract: A microwave heated methyl trichlorosilane based chemical vapour infiltration technique has been used to form SiC f /SiC composites from SiC fibre preforms preimpregnated with SiC powder using two different fabrication techniques. While infiltration rates obtained from samples loaded with powder were generally higher than for preforms without powder, preferential infiltration occurred in regions where the SiC powder was most concentrated as a result of the initial non-uniform distribution of the powder across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This suggests strongly that the powder blocks a significant fraction of the gas paths necessary for CVI. Subsequent work, however, demonstrated that all of the preforms could be successfully infiltrated by CVI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests strongly that the powder blocks a significant fraction of the gas paths necessary for CVI. Subsequent work, however, demonstrated that all of the preforms could be successfully infiltrated by CVI.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests strongly that the powder blocks a significant fraction of the gas paths necessary for CVI. Subsequent work, 39 however, demonstrated that all of the preforms could be successfully infiltrated by CVI. Finally, it should be noted that while no mechanical test data were gathered for any of the impregnated preforms produced in this work, those processed by VB were thinner, stronger, very handleable, and less susceptible to delamination compared with the other methods.…”
Section: Vacuum Baggingmentioning
confidence: 99%
“…They also observed the densification from the inside out, and found that an initial inverse temperature profile is obtained but gradually flattened out after the densification front moved toward the edges. Binner et al 8 applied microwave-assisted CVI to form SiC 𝑓 ∕SiC composites with SiC powder, and reached the average densities as high as 75% after 10 h. D'Ambrosio et al 9 described the design of a pilot-scale microwave-assisted CVI plant in Europe. The reactors in the pilot plant target are able to scale up the size of SiC preforms up to twice of the size of lab-scale ones.…”
Section: Introductionmentioning
confidence: 99%
“…They also observed the densification from the inside out, and found that an initial inverse temperature profile is obtained but gradually flattened out after the densification front moved toward the edges. Binner et al 8 . applied microwave‐assisted CVI to form SiCf/SiC${\rm SiC}_f/{\rm SiC}$ composites with SiC powder, and reached the average densities as high as 75% after 10 h. D'Ambrosio et al 9 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, by using microwaves to enhance the CVI process [37,38], fabrication times can be reduced from several hundred hours to around 100 hours [39,40] and down to only ≈25 hours when RF-CVI is used to produce C 𝑓 -ultra high temperature ceramic matrix composites (UHTCMCs) [41]. Similar results were obtained with the MW-CVI pilot plant developed in the European project HELM for the production of SiC-based CMCs (HELM: High-frequency Electro-Magnetic technologies for advanced processing of ceramic matrix composites and graphite expansion) [42].…”
Section: Introductionmentioning
confidence: 99%